NANODICTIONARY OF SELECTED POLISH ABBREVIATIONS - STOFFA, Ján; STOFFOVÁ, Veronika (Trends in education, 2010)
The nanovocabulary presents a nanodictionary of Polist text abbreviations with their full polish exact wordings and also Czech and Slovak equivalents. The vocabulary was created on a base of excerption from selected original Polish works and is addressed to used wchich aren't proficient in Polish, but they wont to study Polish information sources and have for disposal no special dictionary of Polish abbreviations.
Keywords: Polish-Czech-Slovak dictionary of abbreviations